2004
DOI: 10.1111/j.1460-9568.2004.03116.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus‐induced change in long‐range temporal correlations and scaling behaviour of sensorimotor oscillations

Abstract: The human brain spontaneously generates large-scale network oscillations at around 10 and 20 Hz. The amplitude envelope of these oscillations fluctuates intermittently and was recently reported to exhibit power-law decay of the autocorrelation for hundreds of seconds. This indicates that the underlying networks are in a dynamic state resembling the self-organized critical state known to exist in many complex systems. Based on the mechanism of how correlations emerge in these systems, we hypothesized that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
130
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 51 publications
11
130
2
1
Order By: Relevance
“…A number of studies have reported quadratic rather than linear relationships between alpha power and performance on several tactile tasks (Ai & Ro, 2014;Linkenkaer-Hansen et al, 2004;Weisz et al, 2014;Zhang & Ding, 2010). Typically, in these studies hit rates are highest at an intermediate level of alpha power.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies have reported quadratic rather than linear relationships between alpha power and performance on several tactile tasks (Ai & Ro, 2014;Linkenkaer-Hansen et al, 2004;Weisz et al, 2014;Zhang & Ding, 2010). Typically, in these studies hit rates are highest at an intermediate level of alpha power.…”
Section: Discussionmentioning
confidence: 99%
“…A parabolic relationship between performance and noise is a key characteristic of stochastic resonance. However, these reports in the somatosensory domain have not taken the possibility of changes in false alarm rate with changes in alpha power into account, and thus may have underestimated the downside of variations of alpha power (Ai & Ro, 2014;Linkenkaer-Hansen et al, 2004;Weisz et al, 2014;Zhang & Ding, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations